The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/s002449900309
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Secretory Function Is Enhanced by Low Doses of Tributyltin-Oxide (TBTO), But Not Tributyltin-Chloride (TBTCl)

Abstract: Numerous studies suggest that tributyltin (TBT) is a potent immunotoxicant in nontarget organisms with lymphoid atrophy being a hallmark response. Two of the most common formulations of TBT are bis (tri-n-butyl)-tin oxide (TBTO) and tri-n-butyl-tin chloride (TBTCl). Most of studies investigating TBT-related immunotoxicity have used relatively high doses of both compounds, but little is known about the effects of very low doses. In addition, no studies have directly compared the effects of both formulations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Kergosien and Rice (1998) showed that tributyltinoxide (TBTO) (in a dose up to 3.0 lM/kg of body weight), but not tributyltinchloride (TBTCl), induced a reversible increase in NO production in mouse macrophages. Smith and coauthors (2000) showed that relatively low TBTO concentrations (0.001-0.01 mg/l) induced an increase in NO production in hemocytes of the mussel Mytilus edulis, while high concentrations of the toxicant (0.1 mg/l) significantly inhibited NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Kergosien and Rice (1998) showed that tributyltinoxide (TBTO) (in a dose up to 3.0 lM/kg of body weight), but not tributyltinchloride (TBTCl), induced a reversible increase in NO production in mouse macrophages. Smith and coauthors (2000) showed that relatively low TBTO concentrations (0.001-0.01 mg/l) induced an increase in NO production in hemocytes of the mussel Mytilus edulis, while high concentrations of the toxicant (0.1 mg/l) significantly inhibited NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we cannot rule out the possible involvement of other types of radicals. Indeed Kergosien and Rice (1998) reported that TBT enhances nitric oxide production in macrophages. Therefore, various radicals including nitric oxide may be, in part, involved in TBT toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The four treatment regimens are as follows: (A) undifferentiated cells (monocytes) treated with 10 µM tributyltin-chloride (TBT), a well characterized and highly leukocytotoxic agent (Kergosien and Rice, 1998), as a positive control for cytotoxicity, 10 µM indirubin-3 -monoxime, 1 µM indirubin-3 -monoxime or DMSO as carrier control for 24 hrs; (B) U937 cells were differentiated for 24 hrs in the presence of 0.1 µM PMA, then treated with 10 µM TBT, 10 µM indirubin-3 -monoxime, 1 µM indirubin-3 -monoxime, or DMSO as carrier control for 24 hrs; (C) undifferentiated U937 cells were treated with 10 µM TBT, 10 µM indirubin-3 -monoxime, 1 µM indirubin-3 -monoxime or DMSO as carrier control for 24 hrs followed by a 24-hr period of differentiation in the presence of PMA (effects of treatment on the differentiation process); and (D) U937 cells were differentiated in the presence of 0.1 µM PMA for 24 hrs, the culture medium removed and replaced with fresh media containing 0.1 µM PMA and 1 µg/ml LPS (Salmonella typhimurium; Sigma) for 24 hrs to yield differentiated and activated cells, followed by a 24-hr exposure to 10 µM TBT, 10 µM indirubin-3 -monoxime, 1 µM indirubin-3 -monoxime or DMSO as carrier control. All treatments, including the DMSO carrier control, were conducted in six replicated wells of a 96-well plate per treatment.…”
Section: Cytotoxicity Of Indirubin-3 -Monoxime In U937 Cellsmentioning
confidence: 99%